Complex transition metal hydrides incorporating ionic hydrogen: Thermal decomposition pathway of Na2Mg2FeH8 and Na2Mg2RuH8 - Humphries, Terry; Matsuo, M.; Li, G.; Orimo, S. (Royal Society of Chemistry, 2015)
Complex transition metal hydrides have potential technological application as hydrogen storage materials, smart windows and sensors. Recent exploration of these materials has revealed that the incorporation of anionic hydrogen into these systems expands the potential number of viable complexes, while varying the countercation allows for optimisation of their thermodynamic stability. In this study, the optimised synthesis of Na2Mg2TH8 (T = Fe, Ru) has been achieved and their thermal decomposition properties studied by ex situ Powder X-ray Diffraction, Gas Chromatography and Pressure-Composition Isotherm measurements. The temperature and pathway of decomposition of these isostructural compounds differs considerably, with Na2Mg2FeH8 proceeding via NaMgH3 in a three-step process, while Na2Mg2RuH8 decomposes via Mg2RuH4 in a two-step process. The first desorption maxima of Na2Mg2FeH8 occurs at ca. 400 °C, while Na2Mg2RuH8 has its first maxima at 420°C. The enthalpy and entropy of desorption for Na2Mg2TH8 (T = Fe, Ru) has been established by PCI measurements, with the ?Hdes for Na2Mg2FeH8 being 94.5 kJ mol-1 H2 and 125 kJ mol-1 H2 for Na2Mg2RuH8. This journal is